'Being fair to both sides': an addendum to J.S. Russell's and Mitchell Berman's philosophies of officiating. Issue 3 (1st September 2020) - Dombrowski, Daniel A.
ABSTRACT: It is common to hear the claim that referees in sporting events are doing their jobs well so long as they are, quite simply, being fair to both sides in a competitive event. It will be the purpose of this article to analyze this claim. I will argue that being fair to both sides is, in fact, a necessary condition for good sport officiating, but it is not sufficient. My interlocutors in the article will be J.S. Russell and Mitchell Berman, whose magisterial articles on the philosophy of sport officiating and on the relationship between sport and law rightly emphasize that rules are not all that a referee has to work with while officiating a sporting event. The point to my article is to highlight a feature of rules that is compatible with Russell's and Berman's view that rules are not sufficient: that rules are nonetheless necessary. My thesis is novel because counterintuitive: a referee who is fair to both sides can nonetheless advantage one side over another in a sporting event if the rules (whether de jure or de facto) are not followed. Compelling examples from basketball and baseball and North American football will be used to support my stance.